A post harvest handling systems of sweet peppers (Capsicum annuum) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The requirements of sweet peppers destined for both local as well export markets demand careful attention at every stage from harvest to consumption, if quality is to be achieved and maintained. To effectively maintain quality throughout the market chain and ensure that the required quality is delivered to the recipient market, requires an integrated approach where each part of the post-harvest system, be it sorting, grading, packaging, transportation or storage, must be appropriate to the system as a whole. This manual discusses recent research on methods for the maintenance of sweet pepper quality from the point of harvest to consumption with emphasis on the implications of handling practices adopted at each stage and the effect of such on the final product quality.